2021
DOI: 10.3390/metabo11070427
|View full text |Cite
|
Sign up to set email alerts
|

Primary Metabolite Profile Changes in Coffea spp. Promoted by Single and Combined Exposure to Drought and Elevated CO2 Concentration

Abstract: Climate change scenarios pose major threats to many crops worldwide, including coffee. We explored the primary metabolite responses in two Coffea genotypes, C. canephora cv. Conilon Clone 153 and C. arabica cv. Icatu, grown at normal (aCO2) or elevated (eCO2) CO2 concentrations of 380 or 700 ppm, respectively, under well-watered (WW), moderate (MWD), or severe (SWD) water deficit conditions, in order to assess coffee responses to drought and how eCO2 can influence such responses. Primary metabolites were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 78 publications
1
23
0
1
Order By: Relevance
“…Such enrichment of detox pathways was also accompanied by metabolic and proteomic changes in Icatu, which included the reinforcement of thylakoid electron transport rates and some electron carriers, and the triggering of protective cyclic electron transport involving both photosystems. These processes would help maintain the photochemical use of energy while controlling the presence of reactive molecules of chlorophyll and oxygen [24,25,107]. In this context, the existence of strong post-transcriptional regulations is very likely, probably involving alternative splicing, noncoding RNAs (including siRNA, miRNA, lncRNA), RNA-binding proteins (RBPs) as well as protein modifications [108].…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
“…Such enrichment of detox pathways was also accompanied by metabolic and proteomic changes in Icatu, which included the reinforcement of thylakoid electron transport rates and some electron carriers, and the triggering of protective cyclic electron transport involving both photosystems. These processes would help maintain the photochemical use of energy while controlling the presence of reactive molecules of chlorophyll and oxygen [24,25,107]. In this context, the existence of strong post-transcriptional regulations is very likely, probably involving alternative splicing, noncoding RNAs (including siRNA, miRNA, lncRNA), RNA-binding proteins (RBPs) as well as protein modifications [108].…”
Section: Degs Involved In Phosphatases and Protein Kinases Affected By Droughtmentioning
confidence: 99%
“…Additionally, eCO 2 was recently reported to have also marked implications on how coffee plants respond to soil water deficit, greatly attenuating drought impacts (even under severe water deficit conditions) regarding, among others, the photosynthetic performance, hydraulic conductance, and growth, as well as gene expression and metabolite profile (Avila et al, 2020a,b;Fernandes et al, 2021;Rodrigues et al, 2021;Semedo et al, 2021). When eCO 2 is combined with a single drought episode, high genotypic heterogeneity has been observed in the primary metabolite responses of both C. arabica and C. canephora cultivars (Rodrigues et al, 2021). These findings stress the phenotypic plasticity of the Coffea genome and how it can be harnessed through targeted climate adaptation breeding programs.…”
Section: Coffee Production Under Climate Changementioning
confidence: 99%
“…Recently, studies have demonstrated that the buffering effect of e[CO 2 ] in Coffea plants exposed to different levels of water deficit is genotype-dependent [ 114 , 115 ]. Elevated CO 2 attenuated the negative drought impacts in C. canephora cv.…”
Section: Integrative Responses Of Woody Plants Under Elevated Co ...mentioning
confidence: 99%
“…While in Conilon plants, e[CO 2 ] improved the photochemical efficiency by increasing the PSII efficiency and decreasing the thermal energy dissipation, this beneficial effect in Icatu plants was slight and more related to keeping the abundance of photosynthetic proteins and the cyclic electron flow at PSI under moderate or severe drought conditions [ 114 ]. The contrasting effect of e[CO 2 ] in these Coffea genotypes exposed to different water deficit conditions was also noticed at the metabolic level [ 115 ]. While the abundance of the most primary metabolites (mainly amino acids) decreased in Conilon, they increased in Icatu exposed to the combination of e[CO 2 ] and drought [ 115 ].…”
Section: Integrative Responses Of Woody Plants Under Elevated Co ...mentioning
confidence: 99%
See 1 more Smart Citation